Knowledge Triumphant - Sajjad H. Rizvi (International Institute of Islamic Thought, 2008)
Brill’s new “Classics in Islam” series, a systematic reprinting of some of the seminal works in Islamic studies that have been out of print for decades, is a welcome initiative.As Dimitri Gutas, a former student, indicates in his introduction, Rosenthal’s achievement in this monograph is outstanding within an exceptionally productive and influential career. It is also somewhat unusual that a work first published over thirty years ago still remains unsurpassed, even if one may question some of the argument’s details and tendencies. Rosenthal often worked with manuscripts and unedited sources and, while we have the luxury of criticizing his judgments based on our access to superior critical editions, the contribution of the book remains singular.